2021
DOI: 10.1016/j.apsb.2020.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling in gastrointestinal carcinogenesis and the gastrointestinal tumor microenvironment

Abstract: The Hedgehog (HH) signaling pathway plays important roles in gastrointestinal carcinogenesis and the gastrointestinal tumor microenvironment (TME). Aberrant HH signaling activation may accelerate the growth of gastrointestinal tumors and lead to tumor immune tolerance and drug resistance. The interaction between HH signaling and the TME is intimately involved in these processes, for example, tumor growth, tumor immune tolerance, inflammation, and drug resistance. Evidence indicates that inflammatory factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 159 publications
(153 reference statements)
0
41
0
Order By: Relevance
“…Aberrant activation of Notch signaling has been shown to promote self-renewal in breast CSCs [ 22 , 23 ]. The conserved Sonic Hedgehog signaling pathway modulates a critical stage in the development of an organism, which includes embryonic development, tissue repair, and cell differentiation (this specifically pertaining to gastrointestinal cell lineages) [ 24 , 25 ]. Gene expression analysis of bladder CSCs revealed that upregulation of the Sonic Hedgehog pathway was crucial for self-renewal and population expansion [ 26 ].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Aberrant activation of Notch signaling has been shown to promote self-renewal in breast CSCs [ 22 , 23 ]. The conserved Sonic Hedgehog signaling pathway modulates a critical stage in the development of an organism, which includes embryonic development, tissue repair, and cell differentiation (this specifically pertaining to gastrointestinal cell lineages) [ 24 , 25 ]. Gene expression analysis of bladder CSCs revealed that upregulation of the Sonic Hedgehog pathway was crucial for self-renewal and population expansion [ 26 ].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Tumor-associated macrophages (TAMs) expressing M2 (alternatively activated)-like phenotype imitate type II T-helper cells that express interleukin (IL)-4, IL-5, IL-6, IL-13, and IL-10 to suppress anti-tumor immune response [120,121]. CAF can produce tumor-promoting cytokines such as CXCL12, IL-6, HIF1a, and TGF-b2 [123], and monocytic MDSCs can promote tumor epithelial to mesenchymal transition (EMT) [80].…”
Section: Hedgehog Signaling Suppresses Anti-tumor Immune Responsementioning
confidence: 99%
“…The targeted inhibition of Smo and Gli1 activity has provided information on the role of the Hh/Ptch pathway in the immune response against tumour cells. Thus, Hh signalling influences the activity of macrophages in the tumour microenvironment [ 11 , 12 , 13 ], as well as the activation of T lymphocytes [ 3 , 4 , 14 , 15 ] and the polarisation of T cells towards different T helper (Th) cell phenotypes (Th1, Th2 and Th17) [ 16 , 17 , 18 , 19 ] and modulates the development of different inflammatory pathologies, such as arthritis, pancreatitis, dermatitis, intestinal inflammations or experimental autoimmune encephalomyelitis (EAE) [ 18 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%